Otra ciudad es posible - Faraci, Mg. Arq. Mariano (Universidad Nacional del Litoral, 2015)
Recognizing as central problem the unsustainability of the model of expanded city, on the one hand, and the expulsion of population that suppose certain interventions in the existing city, for other one; across successive investigations has been inquired about how to intervene in the city built contributing to sustainability and quality of life, preventing unwanted and counterproductive phenomena such as unlimited expansion and population expulsion, taking as three central ideas: One, articulate an action tending to repopulate the Center, renewing and re–densifying the neighborhoods of the peri–center, structuring and completing his peripheral neighborhoods. Two, in these three ambits, articulate three instances of work: housing, social equipment and public space as structuring. Three, in turn, the above mentioned, crossed by three conceptual and design axes: quality of life, capacity of adjustment to the changes, and sustainable materiality. The present article, which one proposes in the category of article of reflection, takes again those elaborations for from there thinking about the need of the major and more compromised (with the rights partner spatial) intervention on the soil and real–estate market, with recover of added value by the State, in the frame of a general plan as way towards the construction of a democratic, plural and inclusive city.